The Challenges and Prospects of Georgia’s Transit Potential in the Context of the Formation of a New Transportation and Logistics Hub - Teona Kontselidze, Teona (European Journal of Sustainable Development, 2025)
The main objective of the study is to examine the state of Georgia’s logistics infrastructure; also, to assess the potential for the development of the logistics sector and to consider how the country can maximize its location to promote economic growth and international integration. The subject of the study is Georgia’s transport and logistics infrastructure and its place in the regional and international logistics network. The scientific novelty of the research lies in the fact that it provides new, innovative insights and recommendations for maximizing the potential of Georgia as an international logistics hub. It is based on a complex analysis of Georgia’s geographical location, transport infrastructure and international cooperation and includes a path for the effective functioning of national and international logistics networks. What is new in this research is the preparation of strategic recommendations, which are designed taking into account international standards and experience. Georgia’s logistics and transport sector has been the center of much attention in recent years; however, due to the problems still existing in this area, faulty infrastructure and monopoly structures, the full potential of the sector is untapped. International and regional studies indicate that Georgia plays an important role in the transport and logistics network connecting Europe and Asia. Keywords: international logistics, public spending, economic development, structural analysis of spending, globalization